GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, TAX AVOIDANCE TOWARDS FIRM VALUE - Indriastuti, Maya; Chariri, Anis; Fuad, Fuad (Faculty of Economics and Business, University of Pasundan, 2023)
This research investigates the role of tax avoidance in mediating the effect of GCG and CSRD on firm value. In this study, the samples were 31 manufacturing companies in the 2016-2019 period with 124 annual report that were processed using SEM-PLS. The results showed that institutional ownership and CSRD did not affect tax avoidance. Meanwhile, the independent board of commissioners affected tax avoidance. Institutional ownership had a negative effect on firm value. Further, independent board of commissioners, CSRD, and tax avoidance positively affected firm value. In this study, tax avoidance could mediate an independent board of commissioners on firm value but failed to mediate the effect of institutional ownership and CSRD with firm value.